Pengaruh Lingkungan Kerja, Keselamatan Kerja dan Kesehatan terhadap Kinerja Karyawan - Muhammad Labeeb; Bima Dian (PT. Arsil Reka Engineering, 2023)
Motivation is an inner or psychological process that occurs in a person who is strongly influenced by several factors, namely internal factors and external factors. These internal factors are factors that are inherent in every human being such as nature, experience, level of education, desires and hopes for the future. While external factors are the environment / working conditions, leadership and leadership. Robbins and Coulter (2010: 109) state that motivation is a process in which a person's efforts are energized, directed, and sustained towards achieving a goal. One of the intended goals is to achieve high performance, such as the theory put forward by Mangkunegara (2009:67) that motivation is one of the factors that influence performance. The results of research by Rizal et al (2014) found a significant and positive effect of motivation on employee performance.